Religion, Politics, and Violence in Indonesia Learning from Banser's Experience - Ali-Fauzi, Ihsan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
Banser's history reflects an attempt by religiously minded people, namely the so-called traditionalist NU leaders, to use violence to serve their political interests. Two assumptions about the connection between violence, politics and religion are: (1) that violence is necessary to achieve political ends; and (2) that violence is religiously controllable. When they finally agreed to establish Banser during the colonial era, NU leaders generally accepted these two assumptions and acted accordingly because they were, along with other parts of Indonesian society, struggling to win independence. While independence was indeed won, the same assumptions remain. This is because the state's security apparatus is unable or unwilling to monopolize the use of violence, hence providing paramilitary organizations like Banser with the opportunity to operate.DOI: 10.15408/sdi.v15i3.524